Hangboard training in advanced climbers: A randomized controlled trial - Saskia Mundry (Nature Portfolio, 2021)
Abstract Improving climbing performance strongly depends upon effective training methods. Hangboard training is one of the most popular approaches to increase finger and forearm strength. Training protocols are based on maximizing weight or minimizing edges. We aimed to evaluate which of these protocols was superior. We prospectively analyzed 30 intermediate to advanced climbing athletes [Union Internationale des Associations d'Alpinisme (UIAA) VI–VIII] and randomized them into three groups: control group C (Control, normal climbing training), hangboard group HE (Hang endurance, grips to hold for a determined time decreased every week), and hangboard group HW (Hang weight, + 1.25 kg weight were added each week to hold for a determined time). As endpoints, we measured the grip strength before and after an 8-week training protocol in seven different pinches. Over the 8-week training period, HW hangboard training significantly improved the climbers’ grip strength compared to C [p = 0.032, effect size (ES) 0.36]. Maximizing weight improved the strength in I/II + III, I/II + III + IV and fist significantly. HW was superior compared to C in terms of grip strength improvement in three out of seven pinches and overall grip strength. The overall changes in the HE group did not differ significantly from the C group. An 8-week training protocol with increasing weights (HW) significantly improved overall grip strength more than a regular climbing training without the use of a hangboard.